2016
DOI: 10.1007/s00338-016-1478-0
|View full text |Cite
|
Sign up to set email alerts
|

Visual orientation by the crown-of-thorns starfish (Acanthaster planci)

Abstract: Photoreception in echinoderms has been known for over 200 years, but their visual capabilities remain poorly understood. As has been reported for some asteroids, the crown-of-thorns starfish (Acanthaster planci) possess a seemingly advanced eye at the tip of each of its 7-23 arms. With such an array of eyes, the starfish can integrate a wide field of view of its surroundings. We hypothesise that, at close range, orientation and directional movements of the crown-of-thorns starfish are visually guided. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 56 publications
3
44
0
Order By: Relevance
“…Whereas rhabdomeric opsins have been described in many protostome species as the primary opsin for vision (reviewed in [67] ), no deuterostome eye has previously been found to express an r-opsin. As A. planci eyes have been previously demonstrated to perform proper spatial vision [19][20][21] , our findings thus provide first evidence for a deuterostome eye utilizing an r-opsin for spatial vision.…”
Section: Rhabdomeric Opsinsupporting
confidence: 64%
See 1 more Smart Citation
“…Whereas rhabdomeric opsins have been described in many protostome species as the primary opsin for vision (reviewed in [67] ), no deuterostome eye has previously been found to express an r-opsin. As A. planci eyes have been previously demonstrated to perform proper spatial vision [19][20][21] , our findings thus provide first evidence for a deuterostome eye utilizing an r-opsin for spatial vision.…”
Section: Rhabdomeric Opsinsupporting
confidence: 64%
“…They are compound eyes and structurally they resemble the eyes of arch clams and fan worms [17,18] with lensless ommatidia typically 20-40 µm in diameter. Depending on species, adult specimens have 50-300 ommatidia in each eye and recent studies have shown that this supports spatial resolution in the range of 8-17 degrees used for navigation [19][20][21] . These studies have also indicated that the ommatidia have a single population of photoreceptors which utilize an opsin with peak sensitivity in the deep blue part of the spectrum around 470 nm.…”
Section: Introductionmentioning
confidence: 84%
“…The infrared spectrum is beyond the detection range of starfish photoreception (425-580 nm) and therefore does not interfere with overlying photoperiod lighting 64,65 . The tanks were exposed to regional photoperiod changes (19.25° S, 146.8° E) with full sunlight spectrum plasma units (Luxim Model GRO-41-01, Luma America) with crepuscular twilight ramping.…”
Section: Letter Researchmentioning
confidence: 99%
“…Suzuki et al [149] reported large numbers of adult CoTS moving across shallow sand flats in Ishigaki Island, southern Japan, which were in very poor condition and ultimately became stranded at low tide. For the most part, adult CoTS in good condition and with reasonable access to coral prey will have limited impetus to move, whereas individuals that are starving are probably unlikely to succeed in traversing large distances between reefs, despite demonstrated capacity for detection of reef structures and selective migration toward coral-rich areas via "vision" or chemoreception [150][151][152][153]. It is very likely that CoTS can and do move between close positioned reefs, especially where there is contiguous reef habitat connecting reefs, but the limited temporal and spatial scales of previous movement studies (as well as the predominant focus on movement within coral habitats) do not really inform the capacity of CoTS to travel large distances between reefs.…”
Section: Question 1 (Adults)-are Adults Capable Of Moving Between Reefs?mentioning
confidence: 99%